Investigation of Molecular Diffusion in Hydrogel by Electronic Speckle Pattern Interferometry - Zhang, Xianmin; Hirota, Naoki; Narita, Tetsuharu; Gong, Jian Ping; Osada, Yoshihito; Chen, Kangsheng (The journal of physical chemistry. B, 1999)
The technique of real-time electronic speckle pattern interferometry (ESPI) is proposed to study the diffusion process of surfactants and proteins in gels. The diffusion coefficient is simply and directly determined from the interferograms. The experiments were carried out on a series of surfactants as well as on a myoglobin diffusion in agarose gels. The agreement of the diffusion coefficient values obtained from ESPI with those obtained by electrical conductance measurement or the reported data demonstrates the usefulness of the method. Moreover, spatial distribution of refractive index change in the gel can be determined by phase evaluation. Fick's law for diffusion is utilized to analyze the spatial distribution of the diffuser concentration curves in gel, which are compared with experimental data. We find that the agarose gel in surfactant solution shrinks slightly, which increases the density of the gel and leads to the additional refractive index change. The effect of gel shrinking to surfactant diffusion is discussed, and the distribution of density variation of the gel with time is evaluated.